Innovation in the Professional Formation and Development of Future Teachers - Tsiuniak Oksana; Yaremchuk Nataliya; Haliuka Olha; Prots Marta (Insight: the psychological dimensions of society, 2024)
The aim of the empirical research is to find out and substantiate the psychological content parameters of innovation in the professional formation and development of future teachers. The tasks are: determination of correlations of parameters of higher education students’ professional readiness for innovative activities with independent variables; finding statistically significant differences between the respondents in the samples of bachelors (group I) and master’s students (group II); comparison of the researched groups with high and low levels of the formation of the coefficients of innovation. Methods: retrospective analysis, generalization, systematization and comparison; the author’s questionnaire “Professional readiness of students for innovative activities” (RIA) (Tsiuniak, 2021); method “Diagnostics of the motivational structure of the personality” (DMSP) (Milman, 1990); method “Teacher’s abilities for creative self-development” (TACSd) (Nikishina, 2009). Results. It was found that there are no statistically significant differences in the determined parameters between the samples of bachelors (group I) and master’s students (group II). A positive tendency was stated in group I in the quantitative coefficient of innovation QCI (М=.68; SD=.22; Me=.68) and in group II – the qualitative coefficient of innovation Q2CI (М=.62; SD=.23; Me=. 61). It was established that the coefficients of innovation have four statistically significant correlations with independent variables: creative activity, social usefulness, active self-development, stopped self-development (р<.050; р<.010). Significant differences were found in the studied groups with high and low levels of formation of the quantitative coefficient of innovation (QCI) and the qualitative coefficient of innovation (Q2CI). Discussion and сonclusions. It was explained that the statistically significant correlation between Q2CI and the “social usefulness” parameter is evidence that the subjects are ready to bear social responsibility for innovation, take a mature social position and work for the long term. The obtained empirical results should be taken into account by the organizers of the educational process and the guarantors of specialized educational and scientific programs, who are responsible for future teachers’ academic and professional training.